2017
DOI: 10.3389/fneur.2017.00522
|View full text |Cite
|
Sign up to set email alerts
|

Somatotopy in the Medullary Dorsal Horn As a Basis for Orofacial Reflex Behavior

Abstract: The somatotopy of the trigeminocervical complex of the rat was defined as a basis for describing circuitry for reflex behaviors directed through the facial motor nucleus. Thus, transganglionic transport of horseradish peroxidase conjugates applied to individual nerves/peripheral receptive fields showed that nerves innervating oropharyngeal structures projected most rostrally, followed by nerves innervating snout, periocular, and then periauricular receptive fields most caudally. Nerves innervating mucosae or g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 91 publications
0
16
1
Order By: Relevance
“…The "activation" of MG was most prominent in laminae I-II, decreased in laminae III-IV, and was essentially absent from the deeper laminae. Medio-laterally, it covered the lateral 4/5 of the nucleus, which somatotopically barely exceeds the target region for IoN afferents toward adjacent terminal territories of the ophthalmic (ventrolaterally) and mandibular (dorsomedial) trigeminal branches (Hayashi, 1982;Jacquin et al, 1986;Panneton et al, 2017;Fernández-Montoya et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The "activation" of MG was most prominent in laminae I-II, decreased in laminae III-IV, and was essentially absent from the deeper laminae. Medio-laterally, it covered the lateral 4/5 of the nucleus, which somatotopically barely exceeds the target region for IoN afferents toward adjacent terminal territories of the ophthalmic (ventrolaterally) and mandibular (dorsomedial) trigeminal branches (Hayashi, 1982;Jacquin et al, 1986;Panneton et al, 2017;Fernández-Montoya et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The trigeminal primary afferents pass into the brainstem and terminate in the trigeminal brainstem sensory nuclear complex (subnuclei interpolaris, oralis and caudalis) . The subnucleus caudalis has been specifically implicated in orofacial nociceptive mechanisms, and it is compared to the spinal dorsal horn due to its many analogous morphological and physiological features and now it has been termed the medullary dorsal horn . In these regions, the afferent nociceptive fibres release neuropeptides (substance P and ATP) and excitatory amino acids such as glutamate, that increasingly excite nociceptive neurons (nociceptive‐specific, NS; and wide dynamic range, WDR), a process known as central sensitisation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has shown that, in rats, CFA administration into the TMJ induces an increase in the calcitonin gene‐related peptide (CGRP), nerve growth factor (NGF), interleukin‐1β (IL‐1β) and tumour necrosis factor‐α (TNF‐α) levels, until 6 weeks after administration . Inflammation in the TMJ region results in increased excitability of the trigeminal subnucleus caudalis, which is a sensory nucleus with a laminated structure similar to the spinal dorsal horn and, due to this close similarity has been termed the medullary dorsal horn …”
Section: Introductionmentioning
confidence: 99%
“…According to Terayama et al [ 116 ] and Panneton et al [ 117 ], the central afferent innervations of the IoN are mostly distributed in (but not restricted to) the dorsal and lateral part of the Sp5C, projecting to all the laminae. The pattern of CGRP and SP protein related to the painful component of the IoN was investigated in the superficial laminae of the Sp5C.…”
Section: Methodsmentioning
confidence: 99%